Development and mechanical behaviour of ultra-high-performance seawater sea-sand concrete. Issue 14 (October 2019) - Teng, Jin-Guang; Xiang, Yu; Yu, Tao; Fang, Zhi
Ultra-high-performance concrete is typically defined as an advanced cementitious material that has a compressive strength of over 150 MPa and superior durability. This article presents the development of a new type of ultra-high-performance concrete, namely, ultra-high-performance seawater sea-sand concrete. The development of ultra-high-performance seawater sea-sand concrete addresses the challenges associated with the shortage of freshwater, river-sand and coarse aggregate in producing concrete for a marine construction project. When used together with corrosion-resistant fibre-reinforced polymer composites, the durability of the resulting structures (i.e. hybrid fibre-reinforced polymer–ultra-high-performance seawater sea-sand concrete structures) in a harsh environment can be expected to be outstanding. The ultra-high strength of ultra-high-performance seawater sea-sand concrete and the unique characteristics of fibre-reinforced polymer composites also offer tremendous opportunities for optimization towards new forms of high-performance structures. An experimental study is presented in this article to demonstrate the concept and feasibility of ultra-high-performance seawater sea-sand concrete: ultra-high-performance seawater sea-sand concrete samples with a 28-day cube compressive strength of over 180 MPa were successfully produced; the samples were made of seawater and sea-sand, but without steel fibres, and were cured at room temperature. The experimental programme also examined the effects of a number of relevant variables, including the types of sand, mixing water and curing water, among other parameters. The mini-slump spread, compressive strength and stress–strain curve of the specimens were measured to clarify the effects of experimental variables. The test results show that the use of seawater and sea-sand leads to a slight decrease in workability, density and modulus of elasticity; it is also likely to slightly increase the early strength but to slightly decrease the strengths at 7 days and above. Compared with freshwater curing, the seawater curing method results in a slight decrease in elastic modulus and compressive strength.